The history of translation. Its importance in translation, its teaching through a multimedia multilanguage education program - Delisle, Jean; Salvetti (TRADUCTORA), Anna Maria (Íkala, Revista de Lenguaje y Cultura, 2003)
This talk illustrates why the study of the history of translation is essential in a translating program. Some of its historical functions are described, as well as some different sub-themes of related research. The principal objectives of a course on the history of translation are mentioned, and finally innovative multimedia and multilingual programs on this theme are presented. Received: 23-04-03 / Accepted: 05-06-03. How to reference this article: Delisle, J. (2003). La historia de la traducción: su importancia para la traductología y su enseñanza mediante un programa didáctico multimedia y multilingüe. Íkala. 8(1), pp. 221 – 235